Core Lung Biopsy for Biomarker Analysis. Issue 5 (September 2015) - Sheth, Sujay; Jilani, Danial; Bos, Aaron; Ahmed, Osman; Patel, Mikin; Zangan, Steven
<x xml:space="preserve">Abstract</x> Purpose: The aim of the study was to compare the rate of pneumothorax and chest tube placement in patients undergoing conventional lung biopsy with those undergoing core lung biopsy for biomarker analysis. Materials and Methods: Twenty-three patients had biopsies performed for biomarker analysis (5 male, 18 female patients, mean age 67 y), and 173 patients underwent standard diagnostic lung biopsy (86 male, 87 female patients, mean age 68 y). All biopsies were performed under computed tomography guidance using the coaxial technique (19 G introducer needle and 20 G core biopsy needle). The number of core samples was noted for each case, and all complications were recorded in accordance with Society of Interventional Radiology guidelines. Results: In the biomarker analysis group, a mean of 5.1 core samples (range, 1 to 10) was obtained. In the conventional biopsy group, a mean of 2.9 core samples (range, 1 to 6) was obtained. The pneumothorax rate was 37.6% in the conventional biopsy group and 30.4% in the biomarker analysis group (P=0.505). The rate of chest tube placement was 16.8% in the conventional biopsy group and 8.7% in the biomarker analysis group (P=0.319). Lesion size was found to be an independent predictor of pneumothorax (P=0.031), whereas biopsy tract length was found to be an independent predictor of both pneumothorax (P<0.001) and chest tube placement (P=0.005) upon multivariate analysis. Conclusions: There is no statistically significant difference in the incidence of pneumothorax or chest tube placement between patients undergoing standard diagnostic lung biopsy and those requiring increased core samples for biomarker analysis.